Modeling of marine gas turbine combustor under non-reacting and reacting conditions - Jyothishkumar, V; Ganesan, V (Journal of Naval Architecture and Marine Engineering, 2009)
Present work is concerned with the flow field analysis inside a marine annular gas turbine combustor under non-reacting as well as reacting flow conditions. Three-dimensional gas turbine combustor of 20-degree sector geometry has been created and meshed using the pre-processor GAMBIT. Flow through the combustor has been simulated using FLUENT code by solving the appropriate governing equations viz. Conservation of mass, momentum and energy. The RNG k-Îµ turbulence model is used for physical modeling. Combustion has been modeled using the Probability Density Function (PDF) approach. Total pressure loss has been studied for the isothermal as well as reacting flow case. For reacting flow overall pressure loss across the combustor has been evaluated. Keywords: Combustor, Recirculation region, Non-reacting flow. doi: 10.3329/jname.v2i1.2027 Journal of Naval Architecture and Marine Engineering 2(1)(2005) 21-32